SOME CLINICAL & SEROLOGICAL OBSERVATION ON RINDERPEST IN SHEEP AND GOATS IN AN ENDEMIC AREA IN IRAQ - Salameh, Barhoom (The Iraqi Journal of Veterinary Medicine, 1988)
This study was conducted as an attempt to determine the epidemiology of rinderpest in Awassi sheep and Levantine goats in an area endemic to rinderpest. A herd of sheep and goats that were in contact with cows and buffalo that were infected with rinderpest was examined. Naturally, blood serum samples were collected and examined using an agricultural neutralization test prepared from the kidneys of calves. We did not observe any clinical signs in sheep and goats that lived in coexistence with cows and buffaloes infected with rinderpest.This study demonstrated the absence of antibodies to rinderpest infection in the sera of the sheep and goats that were examined, which indicates the absence of hidden rinderpest infection.